Changes in Japanese Junior High School Students' Sense of Coherence Before and After the Onset of the COVID-19 Pandemic: A Longitudinal Study of Children and Mothers - Omiya, Tomoko; Deguchi, Naoko; Sakata, Yumiko; Takata, Yuriko; Yamazaki, Yoshihiko (Frontiers in Psychiatry, 2022)
We conducted a longitudinal study to clarify the changes in the sense of coherence (SOC); that is, the ability to cope with stress successfully, of 166 Japanese junior high school students and their mothers before and after the onset of the COVID-19 pandemic. First, we analyzed changes in SOC at three time points for all students and divided them into two groups: Group 1 included students with SOC scores that increased or maintained before and after the onset of the pandemic and Group 2 included students with decreased SOC scores after the onset of the pandemic. Second, we conducted a comparative analysis between the two groups. Overall, results indicated that students’ SOC scores increased. Additionally, interpersonal stress scores were lower after the onset of the pandemic than before. There were almost no differences in family relationships, financial conditions, or personality tendencies between the two groups. However, Group 2 did not regain their sense of belonging to school. In this group, the frequency of stress experiences in club activities after the onset of the pandemic, troubles with the opposite gender, and inability to catch up with the contents of the subject lecture were high. The accumulation of small stressors may have hindered the maintenance of a sense of school affiliation. Mothers of students in Group 2 either were full-time employees at baseline or had started a new job after the onset of the pandemic. Their children may have been affected by the households’ damaged financial budget and changes in mothers’ working styles. As COVID-19 reduced the number of days students went to school, students’ SOC could have reduced had they not felt a sense of presence or belonging due to the lack of participation in club activities, school events, etc. Teachers and mothers should communicate carefully with their students and children, respectively, to develop a sense of belonging.